Developing resilient leaders: a training for students - Jansen, Amy L.; Wieland, Alice (Journal of Leadership Education, 2024)
This assignment is designed to enhance resilience among students in leadership courses. It leverages the US Army’s Master Resilience Training (MRT) framework and positive psychology to develop resiliency skills.A three-part experiential workshop integrates academic readings (providing a foundation of resilience concepts), explores the influence of personal identities on leadership and connects leadership skills with resilience concepts.Participants reflect on self-awareness tools and positive psychology and create personalized action plans. Participants' resilience skills are enhanced with their personalized resiliency plan.The program provides a structured approach to resilience training, which can be integrated into university curriculums. Students gain self-awareness and psychological tools to manage challenges, which are valuable for personal growth and professional development. There is a persistent gender gap in leadership, and for women to attain greater parity in leadership positions, resilience skills are imperative. By focusing on identity-related factors, the program prepares future leaders for challenges in attaining leadership positions.This program is uniquely tailored for students aspiring to leadership positions, with an emphasis on the role of identity, such as gender, in leader emergence and overcoming related challenges.
Keywords: dept.lib; peer-reviewed

The interplay of power, incentives, academic freedom, and gender equity - Wieland, Alice; Jansen, Amy (Journal of Academic Freedom, 2024)
Alice Wieland and Amy Jansen explore the intersection of how power, adverse incentives, and gender bias combine to perpetuate gender inequity in higher education.
Keywords: dept.lib; dept.mgt

With Death, an Orange Segment Between Our Teeth, poems by Marie-Claire Bancquart - Bancquart, Marie-Claire (Orison Books, 2023)
With Death, an Orange Segment Between Our TeethMarie-Claire BancquartTranslated from the French by Wendeline A. Hardenberg *Available for pre-order.* Orison Bookspaper / 178 pp. / $18.00bilingualISBN: 978-1-949039-42-9Distributed to the trade by Itasca Books952-223-8373 / orders@itascabooks.comPublication Date: November 7, 2023 ABOUT THE BOOK Marie-Claire Bancquart (1932–2019) was a prolific and prize-winning French poet, novelist, essayist, and critic. In her poetry, she combines an erudite vocabulary and references to classical literature with an earthy sensibility and a fascination with experiencing the smallest moments of everyday life fully. The deceptive simplicity of her poems lays bare the mysteries underlying the world we inhabit and our very existence. Wendeline A. Hardenberg’s careful and skillful translations are sure to broaden the audience for this significant poet as yet too little known outside of France. PRAISE Deeply philosophical, these poems, originally published in French when the author was in her seventies, focus on the meaning of existence. The poet reminds us that our lives—“seven liters of water wrapped in skin”—are “small,” but “the universe [is] in us / us in the universe.” From our “ephemeral perch on the earth,” writing achieves a kind of immortality, producing “a few words warmed by the journey, / that scatter outside, vouching / that you gave them a little extra life.” Readers will be grateful to Hardenberg for carefully shepherding these provocative poems into English. —Nancy Naomi Carlson, recipient of The Oxford-Weidenfeld Translation Prize Strange and wonderful translations of strange and wonderful poems... Marie-Claire Bancquart’s voice is utterly unique; her poems—by turns lyrical and jarring, mystical and forthright, tender and brutal—sing and clamor in your head long after you’ve read them. Like their French originals, Hardenberg’s excellent translations glitter and dart and unsettle; they dodge like wrestlers, then they grab you by the throat and won’t let go. This is rich writing to come back to again and again; each time you’re ambushed by some startling image or phrase or notion that you hadn’t noticed before. A vital book, both in the sense of its aliveness and its urgency.—Bill Johnston, recipient of The PEN Translation Prize ABOUT THE AUTHOR & TRANSLATOR Marie-Claire Bancquart (1932–2019) was a prolific and prize-winning French poet, novelist, essayist, and critic, as well as a Professor Emerita of French literature at the Sorbonne. Her final book, De l'improbable, précédé de Mo(r)t, was published by Éditions Arfuyen in 2020. Wendeline A. Hardenberg studied at Smith College and Indiana University, where she earned master’s degrees in Comparative Literature with a focus on translation and Library Science. She is the translator of numerous books, including The Bookshop of Forgotten Dreams by Emily Blaine, Will You Ever Change? by Aurélie Valognes, and Project Anastasis by Jacques Vandroux. Hardenberg’s translations have been published in Asymptote, Columbia Journal, Metamorphoses, Tupelo Quarterly, Two Lines, and other places. She lives in New Haven, Connecticut. SAMPLE POEM Close The blackberriesare clotted profusely in the bushes we are so close to the secret of this worldthat it seems to be awaitingjusta small steplike onto a balcony, to smell a flower. We don’t move that would be to wound the beingalmost managing to bein view of the fruits’ black boiling.
Keywords: dept.lib; literary-poetry

Exploring the Use of Common Strict Search Criteria in Nursing Literature Searches - Truex, Eleanor Shanklin; Spinner, Emily; Hillyer, Jean; Ettien, A'Llyn; Wade, Sarah; Calhoun, Courtney; Wolf, Grace; Hedreen, Rebecca; Heimlich, Layla; Nickum, Annie; Vonderheid, Susan C. (Nurse Educator, 2023)
Background: Health sciences librarians and nursing journal contributors have expressed concern about the impact of using strict parameters when searching the literature. Purpose: The purpose of this study was to explore the use of strict search criteria (eg, 5-year rule, “nurse as author”) by direct care nurses and nursing students. Methods: Fourteen online focus groups were conducted with 54 participants: direct care nurses, health sciences librarians, nursing faculty, and nursing students. Nursing faculty and health sciences librarians were included as participants to add perspective to the origins and effects of the use of stringent search criteria. Results: The majority of the nurses viewed the 5-year rule and nurse as author search limits favorably, while noting that a strict date range may hamper successful searching. Librarians viewed these search criteria more unfavorably but recognized the value of topic-appropriate search limits. Conclusion: Reliance on strict limits can be detrimental to pertinent results; however, appropriate use is essential for relevant results. Pedagogy focused on searching the nursing literature needs to emphasize that limits are tools to be used judiciously.
0 citations (Crossref) [2023-10-31] SCSU link: https://ovidsp-ovid-com.scsu.idm.oclc.org/ovidweb.cgi?T=JS&CSC=Y&NEWS=N&PAGE=fulltext&D=ovft&AN=00006223-900000000-98854&PDF=y
Keywords: dept.lib; peer-reviewed

CT Fishing Report Occurrences - Hedreen, Rebecca; Grace, Sean (Zenodo, 2021)
Dataset of gamefish occurrences as compiled from the Connecticut Fishing Report (2006-2018) and Trophy Fish Report (2009-2018), both published by the Connecticut Department of Energy and Environmental Protection. Compiled as thesis project by Rebecca Hedreen for a Masters of Science in Biology from Southern Connecticut State University, with advisor Dr. Sean Grace.
Keywords: Connecticut; Long Island Sound; coastal fisheries; data collections; dept.bio; dept.lib; estuarine fisheries; fish catch statistics; game fish; geographical coordinates; geographical distribution; sport fishing statistics

Miki Gets Dressed Translated by Wendeline Hardenberg - Babin, Stephanie (Twirl, 2021)
Keywords: dept.lib

Sharing: A Pull-the-Tab Book Translated by Wendeline Hardenberg - Henand, Alice Le (Twirl, 2021)
Keywords: dept.lib

Pull and Play: Pacifier Translated by Wendeline Hardenberg - Henand, Alice Le (Twirl, 2021)
Keywords: dept.lib

SURPRISE! Slide and Play Shapes Translated by Wendeline Hardenberg - Fouquier, Elsa (Twirl, 2021)
Keywords: dept.lib

Animal Friends 1 2 3 Translated by Wendeline Hardenberg - Loupy, Christopher (Twirl, 2021)
Keywords: dept.lib

Ultimate Spotlight: Rain Forest Animals Translated by Wendeline Hardenberg - Laboucarie, Sandra (Twirl, 2021)
Keywords: dept.lib

The Pop-Up Guide: Space Translated by Wendeline Hardenberg - Dussaussois, Sophie (Twirl, 2021)
Keywords: dept.lib

Little Bug on the Move Translated by Wendeline Hardenberg - Babin, Stéphanie (Twirl, 2021)
Keywords: dept.lib

Matching Game Book: Bugs and Other Little Critters Translated by Wendeline Hardenberg - Babin, Stéphanie (Twirl, 2021)
Keywords: dept.lib

Do You Know?: Dinosaurs and the Prehistoric World Translated by Wendeline Hardenberg - Hedelin, Pascale (Twirl, 2021)
Keywords: dept.lib

Do You Know?: Oceans and Marine Life Translated by Wendeline Hardenberg - Babin, Stéphanie (Twirl, 2021)
Keywords: dept.lib

Ultimate Spotlight: Polar Animals Translated by Wendeline Hardenberg - Laboucarie, Sandra (Twirl, 2021)
Keywords: dept.lib

Mr. Lion's New Hair! Translated by Wendeline Hardenberg - Teckentrup, Britta (Twirl, 2021)
Keywords: dept.lib

Magnetology: Animals Translated by Wendeline Hardenberg - Poulain, Maud (Twirl, 2021)
Keywords: dept.lib

The Pop-Up Guide: Vehicles Translated by Wendeline Hardenberg - Poulain, Maud (Twirl, 2021)
Keywords: dept.lib

This Book Can Do Anything Translated by Wendeline Hardenberg - Mory, Tristan (Twirl, 2021)
Keywords: dept.lib

Pull and Play Books: Let's Be Safe Translated by Wendeline Hardenberg - Henand, Alice Le (Twirl, 2021)
Keywords: dept.lib

Do You Know?: Vehicles and Transportation Translation by Wendeline Hardenberg (Twirl, 2021)
Keywords: dept.lib

Do You Know?: Space and Sky Translated by Wendeline Hardenberg (Twirl, 2021)
Keywords: dept.lib

Ultimate Spotlight: Volcanoes Translated by Wendeline Hardenberg - Laboucarie, Sandra (Twirl, 2022)
Keywords: dept.lib

Crack-Crack! Who Is That? Translated by Wendeline Hardenberg - Mory, Tristan (Twirl, 2022)
Keywords: dept.lib

Do You Know?: Earth and Nature Translated by Wendeline Hardenberg - Benoist, Cécile (Twirl, 2022)
Keywords: dept.lib

Do You Know?: Animals of Land, Sea, and Air Translated by Wendeline Hardenberg - Babin, Stéphanie (Twirl, 2022)
Keywords: dept.lib

The Ultimate Book of Water Translated by Wendeline Hardenberg - Baumann, Anne-Sophie (Twirl, 2022)
Keywords: dept.lib

What About: Science Translated by Wendeline Hardenberg - Fichou, Bertrand (Twirl, 2022)
Keywords: dept.lib

The Pop-Up Guide: Natural Wonders Translated by Wendeline Hardenberg - Laboucarie, Sandra (Twirl, 2022)
Keywords: dept.lib

The Bookshop of Forgotten Dreams: A page-turning opposites attract romantic comedy! Translated By Wendeline Hardenberg - Blaine, Emily (One More Chapter, 2021)
Keywords: dept.lib

From La Folie Elisa By Gwenaëlle Aubry Translated by Wendeline A. Hardenberg - Aubry, Gwenaëlle (Columbia Journal, 2021)
From La Folie Elisa By Gwenaëlle Aubry Translated by Wendeline A. Hardenberg
Section: Translation
Keywords: dept.lib

“The Master of Scents” * Fiction * By Vincent Ravalec * Translated by Wendeline A. Hardenberg - Ravalec, Vincent (Aromatica Poetica, 2022)
He was the Master of Scents. He ruled over them, classified them, harnessed them, recombined them, invented them, and above all took care of their dis...
Keywords: dept.lib

Expanding and Improving Our Library’s Virtual Chat Service: Discovering Best Practices When Demand Increases - Fruehan, Parker; Hellyar, Diana (Information Technology and Libraries, 2021)
With the onset of the COVID-19 pandemic and the ensuing shutdown of the library building for several months, there was a sudden need to adjust how the Hilton C. Buley Library at Southern Connecticut State University (SCSU) delivered its services. Overnight, the library’s virtual chat service went from a convenient way to reach a librarian to the primary method by which library patrons contacted the library for help. In this article, the authors will discuss what was learned during this time and how the service has been adjusted to meet user needs. Best practices and future improvements will be discussed.
6 citations (Crossref) [2023-10-31] Number: 3
Keywords: dept.lib; peer-reviewed

Mealtime Translated by Wendeline Hardenberg - Le Hénand, Alice (Twirl Books, 2020)
Little Crocodile, Little Monkey, and all their friends may not like to try new foods or know what to do …
Keywords: dept.lib

Brothers and Sisters Translated by Wendeline Hardenberg - Le Hénand, Alice (Twirl Books, 2020)
Little Crocodile, Little Monkey, and all their friends have siblings—siblings who take their things, make a mess, or just get …
Keywords: dept.lib

Mr. Lion Dresses Up! Translated by Wendeline Hardenberg - Teckentrup, Britta (Twirl Books, 2020)
How exciting! Mr. Lion has been invited to a party! But what will he wear? A handsome suit . . …
Keywords: dept.lib

Trains Translated by Wendeline Hardenberg - Prénat, Sophie (Twirl Books, 2020)
All aboard! Chock-full of fascinating facts, Ultimate SpotlightTM Trains offers young readers a closer look into the marvelous world of …
Keywords: dept.lib

Animals at Night Translated by Wendeline Hardenberg - Hedelin, Pascale (Twirl Books, 2020)
The fluffy feathers of an owl, the bumpy skin of a toad, and the thick fur of a river otter—there’s …
Keywords: dept.lib

Miki Takes a Bath Translated by Wendeline Hardenberg - Babin, Stephanie (Twirl Books, 2020)
Splish-splash! Miki’s taking a bath! Bathtime couldn’t be more fun with Miki showing how it’s done in this delightful pop-up …
Keywords: dept.lib

The Ultimate Book of Horses Translated by Wendeline Hardenberg - Laboucarie, Sandra (Twirl Books, 2020)
Horses are amazing creatures! The Ultimate Book of Horses provides hours of hands-on discovery and includes age-appropriate information on the …
Keywords: dept.lib

Magnetology: Vehicles Translated by Wendeline Hardenberg - Baumann, Anne-Sophie (Twirl Books, 2020)
Take a ride—whether it’s on a boat, plane, or on a rocket ship! Kids can use the 45 magnetic pieces included to fill 5 oversized scenes in this Magnetology™ title. The all-in-one play set features fascinating information, just right for its audience, about all types of vehicles: those that travel on the road, on a farm
Keywords: dept.lib

Who Does What? Translated by Wendeline Hardenberg - Babin, Stephanie (Twirl Books, 2020)
Who gathers honey? Who designs clothes? Who makes lunch for students? So many jobs can be found in this delightful and satisfying sliding panel format for preschoolers. The 36 panels feature jobs in various settings: in the orchestra, at the market, at school, and more! Each new spread offers clues to the right respon
Keywords: dept.lib

Mr. Bear's Birthday Translated by Wendeline Hardenberg - Aracil, Virginie (Twirl Books, 2020)
Mr. Bear is having a birthday party, and everyone is welcome! It doesn’t matter if you’re big, small, don’t have teeth, or are afraid of the dark . . . you’re invited! In this wonderfully illustrated oversize book that celebrates inclusion as well as a special day, Mr. Bear’s Birthday also includes lots of gifts—with f
Keywords: dept.lib

Patience Translated by Wendeline Hardenberg - Le Hénand, Alice (Twirl Books, 2020)
Waiting is not easy, whether it’s waiting to play with a toy or to eat a snack. And Little Kangaroo, Little Cat, and their friends are just not sure that they can be patient. But as their grown-ups show them, being patient doesn’t have to be boring or unbearable. There are many fun things they can do while they wait! C
Keywords: dept.lib

City Mazes Around the World Translated by Wendeline Hardenberg - Babin, Stephanie (Twirl Books, 2020)
From New York City to Tokyo and Berlin to Sydney, the streets of the 15 cities included in this book are filled with a fascinating showcase of local landmarks and awesome attractions. How will you get from the Brooklyn Bridge to Central Park in New York City? Or find your way to Topkapi Palace in Istanbul? Each spread
Keywords: dept.lib

Collecting Citations from Text - Hedreen, Rebecca (2020)
Basic steps and scripts used for translating text citations to bibtex files suitable for loading into citation management software or citation analysis scripts. 3 publically available...
Keywords: dept.lib